0.35 V time‐domain‐based instrumentation amplifier. Issue 21 (1st October 2014) - Mohan, R.; Yan, L.; Gielen, G.; Van Hoof, C.; Yazicioglu, R.F.
Abstract : A time‐domain‐based amplifier concept is proposed to obtain high‐voltage gains with low power consumption and at an ultra‐low supply voltage of 0.35 V. A prototype instrumentation amplifier designed using the proposed technique in the 180 nm technology consumes 210 nW of power and 0.1 mm 2 of the active area.